Design thinking as a start-up business planning strategy - Vnukova, Nataliya; Makovoz, Oksana; Vakareva, Yelyzaveta; Kuzmenko, Tatiana (Współczesne Problemy Zarządzania, 2021)
This article discusses the peculiarities of startup success and the influence of design thinking, which is based on the methodology of solution design with a focus on human consumers, as the end user of a product or service. The startup is the first necessary stage of the life cycle of innovation. In order for the innovation to be successful, the design thinking methodology is used, which increases the predictability of success, speed of market entry and reduction of investment risks in the innovation. Actively working system of support for start-ups is the basis of active innovation activities, increasing the volume of innovative products, export of high-tech products. Development of startup projects is widespread abroad. It was found that the peculiarity of these successful projects is that they bring high profits, as well as raise the level of the economy in their countries. It is stated that it is important to study the issue of successful launch and implementation of startups through the structures that contribute to their development. Moreover, it is obvious that design thinking is the most successful methodology for creating innovations, which is actively used by various world-renowned companies. This article formulates a methodological model of design thinking for the main characteristics of startup success. The implementation of this model includes the following steps: generalization of the “startup” concept, generalization of the “design thinking” concept, identification of the stages of the startup life cycle, systematization of the key components of successfully realized startups, and analysis of the design thinking capabilities of the startup.